Permanent Instability of Preferences after COVID-19 Crisis: A Natural Experiment from Urban Burkina Faso - Delphine Boutin; Laurene Petifour; Haris Megzari (Institute of Labor Economics (IZA), 2023)
The salience of the first Covid-19 crisis over a well-identified period makes it an unexpected and abrupt change in the environment. This study uses the onset of the Covid-19 crisis to empirically examine whether risk and time preferences change in response to this exogenous shock, and whether those variations are temporary or durable. We use an original panel dataset conducted in January 2020 (before any event), in June 2020 (just after the removal of strong economic measures) and in January 2022 among women working in the informal sector in Ouagadougou, Burkina Faso. We use individual fixed effects on the balanced panel to isolate the specific causal effect of the Covid-19 crisis on variation in attitudes toward risk and time. Two time horizons are analyzed: immediately at the end of the economic restrictions (short-term effect), then two years later (medium-term effect). We demonstrate strong preference instability: immediately after the shock of the Covid-19, risk aversion changed over the 6-month period in both the gain (12%) and loss (-47%) domains, while impatience increased by 20%. Eighteen months later, preferences have not returned to their pre-shock level, suggesting an abrupt and permanent effect of Covid-19 on individual preferences. We also show that risk aversion (in both domains) is non-sensitive to actual impacts, but appears to be driven by economic fears and concerns related to the Covid-19 crisis.
Keywords: D8; D9; C93; I18; O55; 330; COVID-19; risk attitudes; impatience; emotions; media exposure